Dualism in the transformation of Balinese ethnic residential architecture in Denpasar - I Kadek Merta Wijaya; I Nyoman Warnata; Ni Wayan Meidayanti Mustika (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
Spatial transformation and building layout of Balinese ethnic dwellings are influenced by the need for residential space and the occupants of the house. The increase in the number of family members in one dwelling impacts increasing the space for living. The development of architectural style as a trend is another factor that changes building layout. This change is a process from the initial state - the spatial and building layout concept of sanga mandala - towards contemporary architecture. These changes are characterized by architectural elements that are subject to change, and the elements that are persistent to change. This research aims to examine the meaning of dualism in the residents of ethnic Balinese residences as a transformation process. The method used in this research is qualitative content analysis, with demographic, economic, and architectural trends approaches and perspectives. The interpretation resulted from the occupants' perceptions of transforming the Balinese ethnic residence in Denpasar. This study's findings are the process of changing the spatial planning and architectural structure of Balinese ethnic houses based on the fundamental concept of dualism in a sanga mandala spatial layout through demographic, economic, and developmental approaches to Balinese architectural trends.